Impact on households and critical infrastructures from electricity failure. Two case studies and a survey on public preparedness - Grétar Már Pálsson 1989- (2015)
This thesis studies the impact from electricity failure in Iceland on households and critical infrastructures. Households and critical infrastructures electricity dependence is discussed along with a theoretical identification of impacts towards these two subjects from electricity failure. Risk Assessment Plans for Iceland, Norway and Sweden are compared. The main focus of the comparison relates to how the countries focus on electricity, information and communication technologies and the role of the general public in these plans. Case studies on two recent electricity failure events in Iceland were conducted. Impacts from these events were analysed and evaluated. This process enabled comparison between actual discovered impacts from a real events and those analysed in the beginning of this thesis. Further, two surveys were conducted. One of them aimed to evaluate the perceived and actual preparedness of the general public, in Iceland, regarding electricity failure and the other aimed to evaluate the confidence that stakeholders have in the general public regarding electricity failure. Mannvirkjastofnun